Complete genome sequence of a blaNDM-5-producing Escherichia coli DC71 assigned as ST410-O8:H9 and recovered from a captive giant panda (Ailuropoda melanoleuca) in China. (March 2023) - Ji, Xue; Jiang, Bowen; Feng, Na; Zhu, Lingwei; Liang, Bing; Liu, Jun; Guo, Xuejun; Sun, Yang
ABSTRACT: Objectives: In this study, we report the complete genome sequence of a multidrug-resistant Escherichia coli strain recovered from a fecal sample from a captive giant panda in China. Methods: Antimicrobial susceptibility testing was performed. Genomic DNA from E. coli DC71 was sequenced using a Nanopore PromethION sequencer instrument (Oxford Nanopore Technologies, UK) and MGI High-throughput Sequencing MGISEQ-2000 platforms. The clean reads were de novo assembled using SPAdes v3.11. The complete genome was annotated and analyzed using multilocus sequence typing, serotyping, plasmid replicons, fimH typing, chromosomal point mutations, acquired antimicrobial resistance, and virulence genes with web tools available at the Center for Genomic Epidemiology. Results: The complete genome, 4 991 906 bp in length and comprising 4677 protein-coding sequences, was generated. In silico analysis revealed that E. coli DC71 belonged to the ST410-O8:H9 subclone. A carbapenem resistance gene, bla NDM-5, was located on the pDC71-2 plasmid, coproducing bla TEM-1 . Many other resistance determinants encoded by chromosomes and pDC71-3 were found. The virulence related genes carried by chromosomes were mostly related to enterohemorrhagic E. coli (EHEC) O157:H7. Conclusions: To our knowledge, this is the first complete genome of an E. coli ST410-O8:H9 strain recovered from captive giant panda in China. This multidrug-resistant E. coli subclone may pose potential risks to human and animal health. The genome sequence will be helpful to understand the genomic structure, its diversity, and the molecular mechanism allowing bacteria to disseminate the resistance gene.